A real-time algorithm to solve the peer-to-peer ride-matching problem in a flexible ridesharing system - Masoud, Neda; Jayakrishnan, R. (Transportation research. Part B: methodological, 2017)
•An optimal, real-time algorithm for the multi-hop P2P ride-matching problem.•Serving requests as soon as they arrive on a first-come, first-served (FCFS) basis.•Numerical experiments quantify the impact of intersecting rider and driver sets.•Introducing P2P exchange mechanism to reverse the adverse impacts of the FCFS rule. Real-time peer-to-peer ridesharing is a promising mode of transportation that has gained popularity during the recent years thanks to the wide-spread use of smart phones, mobile application development platforms, and online payment systems. An assignment of drivers to riders, known as the ride-matching problem, is a central component of a peer-to-peer ridesharing system. In this paper we discuss the features of a flexible ridesharing system and propose an algorithm to optimally solve the ride-matching problem in a flexible ridesharing system in real-time. We generate random instances of the problem, and perform sensitivity analysis over some of the important parameters in a ridesharing system. Furthermore, we discuss two novel approaches to increase the performance of a ridesharing system.